Comparação de viabilidade de implantação de tratamento de efluente por meio de reator UASB e sistema de lagoas para o município de Peabiru - Paraná - Cazaroli, Rafael de Bitencourt (2014)
The increasing population and the expansion of inhabited areas becomes increasingly serious problems generated by the lack of sewage treatment. Treatment systems that do not require continuous aeration are shown consistent options to expand the supply of sewage treatment plants in the country, due to lower operating costs compared to aerated systems. The objective of this study was to compare the viability of implementing two distinct systems of treatment, UASB (Upflow Anaerobic Sludge Blanket) and the Australian system of ponds. For the UASB system has been designed with 4 units each with 380m ³. The ponds system has been designed with 2 anaerobic ponds, 3 facultative ponds and 4 maturation ponds, occupying an area of approximately 1.76 hectares. The implementation costs of each system were estimated based on cost curves obtained in the literature and corrected based on the INCC. The UASB system with post treatment had estimated cost of R$ 4.234.691,64 while the ponds system was estimated to cost R$ 4,106,139.70. The difference in cost between the two systems was R$ 128,551.94. The most appropriate system is a Australian ponds sistem, have a more efficient nutrient removal and disinfection, as well as simplified operation and construction. It is concluded that for the city of Peabiru deploying a pond sistem is a viable solution for the sewage treatment.